Synthesis and Characterization of Reduced Graphene Oxide (RGO) as a Solid-State Electrolyte in Batteries - Lela Mukmilah Yuningsih; Devi Indah Anwar; Eva Fauziah (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2025)
Reduced Graphene Oxide (rGO) is a derivative of graphene that has undergone the removal or reduction of its oxygen groups. This study performed the synthesis and characterization of rGO as a solid-state electrolyte in batteries in order to assess the conductivity of rGO and its ability to store electrical currents and voltages. The rGO was synthesized by the Hummers method and the reduction of graphene oxide with a zinc reductor. Graphite oxide was first synthesized by oxidizing graphite with H2SO4 dan KMnO4. This graphite oxide was ultrasonically exfoliated and treated with a Zn reductor to produce rGO in powdered form. The rGO was characterized with Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), an LCR-meter, and a Digital Multimeter. This identified a diffraction pattern in rGO with a 2θ of 25.85° and a d-spacing of 3.444 Å with 48.76 % crystallinity. FTIR observation on rGO exhibited O-H vibrations at a wavelength of 3431.6 cm-1, C=O at 1722.43 cm-1, C=C (1573.91 cm-1), and C-O (1080.14 cm-1). The rGO was observed to have a triple-layered morphology at 10000x magnification. Conductivity for the rGO was identified as 0.000357005 S/cm, while the generated voltage was 1.21 V with a current of 3.55 mA.